Présentation : du fléau social au fait social. L’étude des homosexualités - Chamberland, Line (Sociologie et sociétés, 1997)
En accès libre : https://id.erudit.org/iderudit/001128ar
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; homosexualité; identités LGBTQIA2+; militance; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1183; sexualité; soc2014; sociologie; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Disponible en ligne: https://link-springer-com.proxy.bibliotheques.uqam.ca/article/10.1057/fr.1997.7
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

L'histoire des femmes : construction et déconstruction d'une mémoire sociale - Fahmy-Eid, Nadia (Sociologie et sociétés, 1997)
Cet article analyse le rapport entre la mémoire sociale des femmes et l'histoire féministe qui a vu le jour au cours des trente dernières années. L'hypothèse défendue ici est que mémoire et histoire s'alimentent réciproquement et qu'elles sont toutes deux le fruit d'un construit social. Toutes deux opèrent un tri dans le passé et l'ordonnent selon une perspective particulière. Toutes deux s'inscrivent dans des rapports de pouvoir, rapports qu'elles reflètent en partie, mais qu'elles contribuent également à interroger et à remettre en cause. C'est ainsi que la mémoire des femmes et l'histoire féministe se sont avérées des éléments importants de conscientisation et de changement social.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; mémoire culturelle; pratiques féministes; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Des mots, des pratiques et des risques : la gestion différenciée de la parole et de la prévention du VIH chez des hommes à comportements bisexuels en France - Mendès-Leite, Rommel; Deschamps, Catherine (Sociologie et sociétés, 1997)
Cet article présente une partie des résultats de deux recherches socio-anthropologiques réalisées en France auprès d'hommes ayant des rapports sexuels avec des hommes et des femmes, indépendamment de leur identité socio-sexuelle. Les analyses portent d'abord sur les perceptions différenciées de la sexualité et sur ses conséquences en matière de restitution du sens, et ensuite sur la gestion des comportements préventifs. Ainsi il apparat!, au travers d'une relecture des notions de " multipartenariat ", de " sexe occasionnel " ou de " fidélité ", que le principal lieu de rupture dans la gestion des risques vin est avant tout dépendant de la variable sexe des partenaires sexuels, quand bien même la compréhension de ce mécanisme ne se réduit pas à une opposition basique entre hommes et femmes.
Keywords: 1900-1999; VIH; analyse différenciée selon les sexes -ADS+; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire et politique; hétérosexisme; justice sociale; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité masculine; sociologie; systèmes d'oppressions; thématiques

Le Red light de Montréal - Proulx, Daniel (VLB éditeur, 1997)
"La légende du défunt quartier montréalais dit du "Red Light" vaut bien celle des Soho et Pigalle de ce monde. Prospères au début du siècle, les salles de jeux enfumées et les chambres sordides de nos bas-fonds deviennent dans les années trente les derniers refuges des damnés de la crise. La guerre venue, les entrepreneurs en plaisirs défendus font des affaires d'or, en attendant que l'armée s'en mêle. La guerre finie, le Red Light renaît en force. C'est alors que Pacifique Plante et Jean Drapeau entrent en scène et procèdent à l'épuration radicale de nos moeurs. Le rideau tombe sur notre quartier "réservé". Aujourd'hui, la "Main" n'est plus qu'un coin de rue, à l'intersection de Sainte-Catherine et de Saint-Laurent. Ni ses habitués ni les passants n'ont idée de son spectaculaire passé." – Quatrième de couverture
Section: 83 pages, [32] pages de planches : photographies en noir et blanc ; 23 cm.
Keywords: 1900-1999; amériques; canada; cours; discipline; his4860; histoire; histoire de la sexualité; histoire et politique; industrie du sexe; montréal; premier cycle; périodes historiques; québec; red light; régions géographiques; révolution tranquille; sciences humaines; sexualité; thématiques; travail; travail du sexe

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Universidad Nacional de Quilmes, 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Disponible gratuitement en ligne https://www.marxists.org/espanol/tematica/kiosko/argentina/voz-de-la-mujer/index.htm
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; cours; cycles supérieurs; discipline; europe; fem1000; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires